(untitled) (Journal of the College of Languages (JCL), 2018)
This article briefly analyzing contemporary works appeared in theater writer from Latin America, which comes within the theme of "power." Latin American Literature, such as two-way extremely clear: the vanguard of social and attention, have arrived at certain moments to some extent be regarded as a two-way rival. That desire to participate in the revolution of expression and artistic significance, has appeared evident in the literature of Latin America in the late nineteenth century and ended in the third decade of the twentieth century. The writers that stage would prefer not to serve the objectives of the revolution of Arts own but the objectives of social and political revolution that stimulate the world. These acts were issued in different historical times, characterized by the type of my perception of events, but it is diagnosed as a case of humanitarian power permanently. And it dealt a symbolic study and the concept of "power" in the two works playwrights of the finest writers of Latin America, particularly Mexico, which has suffered in past centuries during the Spanish occupation of the new continent of the authoritarian practices of the authority of the occupier where the subject of power in the history of world literature was the target of a lot of discussions and studies.As for the search axes has been selected the following actions: - "All cats are brown" (1970) Mexican writer Carlos Fuentes Macias, in which the idea of the power comes tightly linking religion and the concept of a world of two different cultures: the culture Alozatkih and Spanish (metaphor cats and color). " Palinuro on the stairs" (1992) Mexican writer Fernando del Paso. This work was part of Tragide- Comedy, from which used elements of "Comedy del Arte" (Commedia dell’Arte) mixed with elements of contemporary theater. Again highlights the subject of power, and in this case comes championed student rebel movement 68 against absolute tyranny (the massacre of students in Talatiloloko) (metaphor climbing stairs).